2007
DOI: 10.1152/ajplung.00308.2006
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin regulates cigarette smoke-induced proinflammatory mediator release via RelA/p65 NF-κB in macrophages in vitro and in rat lungs in vivo: implications for chronic inflammation and aging

Abstract: The silent information regulator 2 (Sir2) family of proteins (sirtuins or SIRTs), which belong to class III histone/protein deacetylases, have been implicated in calorie restriction, aging, and inflammation. We hypothesized that cigarette smoke-mediated proinflammatory cytokine release is regulated by SIRT1 by its interaction with NF-kappaB in a monocyte-macrophage cell line (MonoMac6) and in inflammatory cells of rat lungs. Cigarette smoke extract (CSE) exposure to MonoMac6 cells caused dose- and time-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
368
2
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 368 publications
(407 citation statements)
references
References 35 publications
28
368
2
9
Order By: Relevance
“…NF B activity has previously been shown to be inhibited by Sirt1 (23)(24)(25). We confirmed such inhibition of NF B in embryonic fibroblasts derived from Sirt1-tg mice.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…NF B activity has previously been shown to be inhibited by Sirt1 (23)(24)(25). We confirmed such inhibition of NF B in embryonic fibroblasts derived from Sirt1-tg mice.…”
Section: Discussionsupporting
confidence: 84%
“…IL-6 and TNF␣ are regulated by NF B, which in turn is activated by dietary lipids through the Toll-like receptor TLR4 (5). Interestingly, Sirt1 has been described to inhibit NF B activity (23)(24)(25). To evaluate whether NF B is down-modulated by Sirt1 in our mouse model, we performed the following in vivo and in vitro assays.…”
Section: Transgenic Sirt1 Mice Are Protected From Hepatic Inflammationmentioning
confidence: 99%
“…The results presented here show that SIRT1 represses LEF1 gene expression, which activates MMP13 gene expression. Studies have shown that SIRT1 can demonstrate a broad antiinflammatory function in a variety of tissues (44)(45)(46)(47)(48)(49). For example, in chronic obstructive pulmonary disorder, SIRT1 exerts a protective effect, partially because of its capacity to down-regulate MMP9 (49), and modulating NFkB activity during the disease (48).…”
Section: Sirt1 Represses Mmp13 Gene Expression 3123mentioning
confidence: 99%
“…[21][22][23][24][25][26] Interestingly, Sirt1 expression in the lung is reduced in the elderly who are known to be particularly susceptible to PM-induced cardiopulmonary mortality. 24,33 In this study, we investigated the role of Sirt1 in PM-induced lung coagulation.…”
Section: Introductionmentioning
confidence: 99%